Discussion: Empirical Evidence on Dividends as a Signal of Firm Value - Brickley, James A. (Journal of Financial and Quantitative Analysis, 1982)
James A. Brickley, Discussion: Empirical Evidence on Dividends as a Signal of Firm Value, The Journal of Financial and Quantitative Analysis, Vol. 17, No. 4, Proceedings of the 17th Annual Conference of the Western Finance Association, June 16-19, 1982, Portland, Oregon (Nov., 1982), pp. 501-502